The Effect of a Single Session of Whole-Body Vibration Training in Recreationally Active Men on the Excitability of the Central and Peripheral Nervous System - Chmielewska, Daria (Akademia Wychowania Fizycznego w Katowicach, 2014)
Vibration training has become a popular method used in professional sports and recreation. In this study, we examined the effect of whole-body vibration training on the central nervous system and muscle excitability in a group of 28 active men. Subjects were assigned randomly to one of two experimental groups with different variables of vibrations. The chronaximetry method was used to evaluate the effect of a single session of whole-body vibration training on the excitability of the rectus femoris and brachioradialis muscles. The examination of the fusing and flickering frequencies of the light stimulus was performed. An increase in the excitability of the quadriceps femoris muscle due to low intensity vibrations (20 Hz frequency, 2 mm amplitude) was noted, and a return to the initial values was observed 30 min after the application of vibration. High intensity vibrations (60 Hz frequency, 4 mm amplitude) caused elongations of the chronaxy time; however, these differences were not statistically significant. Neither a low intensity vibration amplitude of 2 mm (frequency of 20 Hz) nor a high intensity vibration amplitude of 4 mm (frequency of 60 Hz) caused a change in the excitability of the central nervous system, as revealed by the average frequency of the fusing and flickering of the light stimulus. A single session of high intensity whole-body vibration did not significantly decrease the excitability of the peripheral nervous system while the central nervous system did not seem to be affected.